The alignment between knowledge strategy and business strategy and its influence on business performance / Shamsul Khairul Annuar Nordin - Nordin, Shamsul Khairul Annuar (2015)
Customers, competitors, and technologies are the influences that make business firm change their strategic direction. Strategic management begins by answering how business firms could achieve competitive advantages in this kind of environment. One of the traditional solutions for business firms to adapt to this kind of environment is to execute business strategies in order to balance between the internal and external environmental factors. However, this does not ensure that the business firms will gain competitive advantages. The knowledge based view is believed to contribute to business firm in achieving competitive advantages and superior performance. Several researchers claimed that knowledge emerged as organization’s crucial assets that play a vital role as a competitive tool and direction for the company to survive and perform in the turbulent environment of business. This encouraged business firms to acquire knowledge management (KM) and have the ability to create, disseminate, use and keep the knowledge asset from being imitated by the competitors.However, simply possessing knowledge does not ensure firms to achieve competitive advantages and it must be aligned with the firm’s business strategy. Additionally, to attain superior performance and competitive advantages it is essential for business firms to fully utilize and integrate its knowledge resources in their business strategy. Therefore, the main objective of this study was to examine the influence of alignment between knowledge strategy and business strategy on hotel business performance. The target populations in this study consist of 73 hotels located in Kuala Lumpur, Selangor and Putrajaya. A variance-based or PLS-SEM and modified alignment formula were applied as main statistical method as to excel research hypotheses and overall research objective. PLS-SEM result has confirmed that both knowledge strategy and business strategy were positively influence hotel performance. Derived from the calculation of alignment formula, most of the hotels have aligned their knowledge strategy and business strategy. PLS-SEM result has also confirmed that those hotel who are highly aligned knowledge strategy and business strategy, performed better than those who are modest in aligning their knowledge strategy and business strategy